THE USAGE OF PAUSE PROCEDURE METHOD DURING DISCUSSION BASED LESSONS - Turdiyeva Zahro Mirsoliyevna (TADQIQOTLAR, 2025)
Abstract Discussion-based lessons have gained prominence as a dynamic and interactive teaching approach that fosters critical thinking, collaborative learning, and active student engagement. This article explores the theoretical and practical aspects of using discussion-based lessons in educational settings. It highlights their benefits in developing communication skills, deepening subject comprehension, and enhancing problem-solving abilities. Additionally, the article addresses potential challenges and offers strategies for effective implementation. By analyzing case studies and relevant research, the study emphasizes the transformative role of discussion-based lessons in both traditional and modern classrooms.